Monitoring COVID-19 Impacts on Household in Lao PDR, Report No. 1 : Results Snapshot from a Rapid Monitoring Phone Survey of Households - World Bank (World Bank, Washington, DC, 2020)
The Coronavirus (COVID-19) pandemic has adversely affected economies around the globe, bringing unprecedented challenges in health, economics and society. Lao PDR has a relatively low number of recorded Coronavirus (COVID-19) cases compared to other economies. To monitor the social and economic impacts of the pandemic, the World Bank conducted a Coronavirus (COVID- 19) rapid monitoring phone survey of households in Lao PDR. This monitoring data helps provide insights into the lingering effects of the pandemic on household well-being as the country entered a post-lockdown economy. The phone survey was conducted from June 20 to July 16, 2020, interviewing 2,500 households from all provinces, in both rural and urban areas. This note provides a snapshot of results from the survey.